Computational study of Klang Valley's urban climatology, and urbanisation of Putrajaya city, Malaysia - Morris, Kenobi Isima (2016)
Urbanisation is associated with physical modifications of land surfaces and climate of a given area. Studies of urbanisation effect on urban climate of Klang Valley region is below par. This research aims to bridge the gap by using a coupled Weather Research and Forecasting (WRF) model with the NOAH Land Surface Model (NOAH) and Urban Canopy Model (UCM) – WRF/NOAH/UCM to investigate the urban climatology of Klang Valley and the urbanisation of Putrajaya over a decade. In addition, evaluation of the garden city concept adopted in the development of Putrajaya city is also conducted. The model is first validated against a network of meteorological observations in the region to determine its suitability for urban climate investigations. Climatological variables (near-surface temperature, relative humidity, and wind speed) along with land use and land cover (LULC) changes; planetary boundary layer height (PBLH), and urban heat/cool islands (UHI/UCI) of the area are also investigated. The model evaluation shows good performance over the region. LULC changes demonstrates strong influence in thermal climatology variations. A mean maximum UHI intensity of ~4.2 ºC was observed in the urban canopy-layer of the Klang Valley.